KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMOTIVASI DAN BUDAYA KERJA TERHADAP KINERJA GURU PADA SMKN DI BANJARBARU - Winda Amalia; Tintin Rostini; Kasypul Anwar (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
This study aims to analyze the role of school principals’ leadership in motivating teachers and to examine how work culture contributes to teacher performance at SMKN 1 Banjarbaru and SMKN 3 Banjarbaru. Effective leadership and a healthy work culture are considered crucial elements in improving the quality of education as well as teacher performance. The research employed a descriptive quantitative method, with interviews as the primary data collection instrument. The participants of this study consisted of principals and teachers from both schools. Data analysis was carried out using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal a significant influence of principal leadership on teacher motivation. Principals who applied transformational leadership—characterized by providing support, recognition, and involving teachers in decision-making—were proven to enhance teachers’ motivation. Furthermore, a positive work culture, reflected in teamwork, effective communication, and a supportive work environment, was also found to have a strong correlation with improved teacher performance. In conclusion, the study highlights that effective leadership and a conducive work culture significantly contribute to teacher performance at SMKN 1 and SMKN 3 Banjarbaru. The recommendations include encouraging principals to continuously develop leadership skills, design more targeted motivation programs, and foster a positive work climate. These efforts are expected to further enhance teacher performance, thereby positively impacting the overall quality of education in SMKN Banjarbaru.